2017
DOI: 10.1002/alr.21986
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual reality as a teaching tool for neuroanatomy

Abstract: Immersive VR educational tools awarded a more positive learner experience and enhanced student motivation. However, the technology was equally as effective as the traditional text books in teaching neuroanatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
280
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(346 citation statements)
references
References 41 publications
10
280
0
14
Order By: Relevance
“…The incentives for immersive VR being incorporated into post-secondary education and skill training may include one or more of the following: the maintenance of ethical principles, overcoming problems concerning time and space, increasing the physical accessibility of environments that are not normally accessible and/or overcoming what would normally be a dangerous situation (Freina and Ott, 2015). Surgical Education's demand for immersive VR can be explained by ethical principles, which allows users to train technical skills without subjecting patients or the users themselves to the possibility of harm (Ziv Health Sciences Anatomy Stepan et al, 2017 Skill Training/Engagement Experiment: Randomized controlled study compared online textbooks with VR HMD (Oculus) to enhance student neuroanatomical knowledge (ventricular and cerebral). HMD VR was shown to be more engaging and similar to online for knowledge acquisition.…”
Section: Where Immersive Vr Was Implementedmentioning
confidence: 99%
“…The incentives for immersive VR being incorporated into post-secondary education and skill training may include one or more of the following: the maintenance of ethical principles, overcoming problems concerning time and space, increasing the physical accessibility of environments that are not normally accessible and/or overcoming what would normally be a dangerous situation (Freina and Ott, 2015). Surgical Education's demand for immersive VR can be explained by ethical principles, which allows users to train technical skills without subjecting patients or the users themselves to the possibility of harm (Ziv Health Sciences Anatomy Stepan et al, 2017 Skill Training/Engagement Experiment: Randomized controlled study compared online textbooks with VR HMD (Oculus) to enhance student neuroanatomical knowledge (ventricular and cerebral). HMD VR was shown to be more engaging and similar to online for knowledge acquisition.…”
Section: Where Immersive Vr Was Implementedmentioning
confidence: 99%
“…In this review, all three studies consulted found no significant differences in the post-test results of HMDs compared with the control alternatives: 2D images (Ekstrand et al, 2018), online textbooks (Stepan et al, 2017), AR tablets, and conventional tablets (Moro et al, 2017). Significant improvement between pre-and post-tests was observed in one study (Ekstrand et al, 2018) but not in another (Stepan et al, 2017). Adverse side effects were measured using a questionnaire in one study, and they found the VR group using HMDs experienced higher levels of side effectsincluding significantly more dizziness, blurred vision and general discomfort -than the AR tablet or tablet groups (Moro et al, 2017).…”
Section: Head Mounted Devicesmentioning
confidence: 83%
“…Whilst research into the pedagogical applications of VR are expanding rapidly, with reviews and speculative studies gradually emerging in the life sciences domain [2,3], experimental studies into applied teaching and learning using fully-interactive VR applications are relatively sparse, although notable exceptions do exist, see Refs. [4,5,6]. The reasons for this apparent exiguity likely stems from the financial and skills investments that VR development requires, but as open access development tools continue to gain traction, this investment is reducing steadily.…”
Section: Introductionmentioning
confidence: 99%